ANALISIS PENINGKATAN PENDAPATAN PETANI SAYURAN DI KECAMATAN TUJUH BELAS KABUPATEN BENGKAYANG MELALUI PERBAIKAN SALURAN DISTRIBUSI - B01111008, Amin Rohman (Jurnal Pembangunan dan Pemerataan, 2015)
Vegetable Farmers' Income Improvement Analysis in District Seventeen Bengkayang by Improved Distribution Channels.This study aims to know (1) the pattern of distribution channel of vegetables that occurred in the District Seventeen, (2) determining the pattern of distribution channels of vegetables that can increase the income of vegetable farmers in the district Seventeen .The method used is a qualitative descriptive study. The study population were vegetable farmers in the District Seventeen. Research subjects are 40 respondents, that farmer who cultivated vegetable tomato, big chili, eggplant, green beans, cucumbers and beans. The used data are primary data taken in February 2015. The data was collected by observation, interviews and open questionnaires method. Using presentation of the questionnaire answers and conclusion data analysis. Based on the research results, we concluded that: first, the distribution channel of vegetable commodities in District Seventeen have four channel, Channel I: Farmers to the Collector, the Collector to Malaysia (exports), Channel II: Farmers to Malaysia (exports ), Channel III: Farmers to Collector of the village, Collector of the village to the merchant outside the city, Channel IV: Farmers to Retailers, retailers to consumers. Second, the distribution channels that can increase the income of vegetable farmers in the District Seventeen is the channels II: From Farmer to Malaysia (exports). Keywords: farmers' income, vegetables commodity, and distribution channels. Â